Selective modification of a native protein in a patient tissue homogenate using palladium nanoparticles. Issue 100 (29th November 2019) - Peramo, Arnaud; Dumas, Anaëlle; Remita, Hynd; Benoît, Mireille; Yen-Nicolay, Stephanie; Corre, Raphaël; Louzada, Ruy A.; Dupuy, Corinne; Pecnard, Shannon; Lambert, Benoit; Young, Jacques; Desmaële, Didier; et al.
Abstract : A chemoselective native protein modification in near-organ medium was achieved using new benign palladium nanoparticles. Abstract : We have developed new benign palladium nanoparticles able to catalyze the Suzuki–Miyaura cross-coupling reaction on human thyroglobulin (Tg), a naturally iodinated protein produced by the thyroid gland, in homogenates from patients' tissues. This represents the first example of a chemoselective native protein modification using transition metal nanoobjects in near-organ medium.